IL RAPPORTO UOMO ACQUA NELLE SCELTE INSEDIATIVE E NELL’ORGANIZZAZIONE ANTROPICA DEL TERRITORIO: IL CONTRIBUTO DELLA CARTA ARCHEOLOGICA DELLA CAMPANIA - Cera, Giovanna (Riparia, 2018)
The following work analyze several aspects concerning the relationship between man and water in the inner landscapes of Northern Campania, in particular in the Upper and Middle Volturno Valley and in the Capua Plain. This analisys is inspired by the results of the topographical surveys made in these territories in the last years (Archaeological Map of Campania). It aims to illustrate the development of the settlement in relation to the waterside zones, in a period between the Prehistory to the Roman Age. According to the available evidences about it, we can highlight some representative cases of forms of land use connected or conditioned by water recources. We can also focus the attention on the cultural and economic dynamics developed in relation to the main rivers and river valleys. Key words: Campania settentrionale; river valleys; water resources; settlement; land use.